Cutaneous leishmaniasis at Wasit governorate - Baghdad Science Journal (مجلة بغداد للعلوم)
The study included identification of Leishmania parasites from cases of cutaneous leishmaniasis, by examination of smears for LD bodies , isolation of parasites by culture in media , and characterisation of the isolated parasites by Isoenzyme analysis.Out of 100 cases suspected for cutaneous leishmaniasis ; 85 were diagnosed on culture for Leishmania promastigotes and this method was found to be superior to direct microscopy for amastgotes (LD bodies) .The cases included in this study belonged to different areas of Wasit/Iraq. There were 30 cases from Hay, 35 from Badra, and 35 cases from Suwaira.The distribution of infection in different age groups indicated that majority of cases belonged to young and middle aged adults. The infection was detected in both sexes with a predominance in males. The clinical picture of cutaneous lesions was suggessive of both wet and dry types of lesions.